[ENG] THE RETOPIAN IMAGINATION // LA IMAGINACIÓN RETÓPICA - Dirk Hoyer (Los Libros de la Corte.es)
Can the current attitudes toward utopia be described as hollow space in the Blochian sense? The political debate is dominated by apocalyptic imagination which fuels populist movements but ultimately it does not have any emancipatory potential. Contemporary reflection on utopia can be either defined by a outopian attitude that is critical towards the status quo but sees alternative arrangements as no-places or as a contemplative utopia, that recognizes the need for utopian visions but cannot identify any political agency. Activism without utopian mental picture often disintegrates for lack of a unified goal and therefore cannot live up to its transformative potential. Retopia, the fourth attitude towards utopia could refocus the eutopian impulse and counter the apocalyptic imagination with a radical imagination that is based on the encouragement of political action. Politics is a confidence game and action inspired by retopian mental pictures could create a sense of an opening in the There is No Alternative doctrine that dominates the political sphere.. KEYWORDS: outopia/eutopia, retopia, action, imagination, political agency